The Tell it! manual : the complete program for evaluating library performance - Zweizig, Douglas (Chicago : American Library Association, 1996)
A step-by-step guide to planning, developing and implementing library evaluation programmes that optimize a library's strengths and its value to the community. The book includes stories from libraries whose programmes have been successful.
Contents: Ch. 1. Overview of TELL IT! / Douglas Zweizig -- Ch. 2. Talk About the Vision: The Heart of Your Library / Jane Robbins -- Ch. 3. Explore Alternatives and Design Your Approach / Douglas Zweizig -- Ch. 4. Learn From What's Happening / Douglas Zweizig -- Ch. 5. Let People Know What Happened : Telling the Story / Amy Owen -- Ch. 6. Integrate Results with Ongoing Services and Think about How It All Worked / Douglas Zweizig -- Ch. 7. Overview of Adult Learning / Robert O. Ray -- Ch. 8. Planning Training Activities: A Checklist / Ruby A. Licona -- Ch. 9. The Evaluation of Continuing Education / Debra Wilcox Johnson -- Ch. 10. Training Outlines and Guidelines / Debra Wilcox Johnson -- Ch. 11. Training in the TELL IT! Approach / Douglas Zweizig -- Ch. 12. Evaluation Methods / Debra Wilcox Johnson -- Ch. 13. Choosing an Evaluation Method / Debra Wilcox Johnson -- Ch. 14. Questionnaires / Keith Curry Lance and Debra Wilcox Johnson -- Ch. 15. Interviewing / Jane Robbins -- Ch. 16. Focus Groups / Debra Wilcox Johnson -- Ch. 17. Gathering Numbers for Evaluation / Douglas Zweizig -- Ch. 18. Observation / Douglas Zweizig and Debra Wilcox Johnson -- Ch. 19. Attitude Measurement / Ronald Powell -- Ch. 20. Making Sense of Narrative Responses / Michele Besant
Includes index.
Keywords: LIBRARIES -- EVALUATION